The Association Between Religious Commitment with the commitment to health behaviors with a focus on Islamic lifestyle - pejman bagheri; zahra akbarzadeh; zahra maleki (Fasa University of Medical Sciences, 2020)
Background & Objective: Modern human suffers from a kind of religious non-alignment along with a health crisis. The aim of this study was to investigate the relationship between religious commitment and commitment to health behaviors with the aim of highlighting the role of spirituality crisis in a health crisis. Materials & Methods: This cross-sectional study was conducted and 310 people in the city of Fasa over 18 years, were randomly selected and then, Worthington religious commitment questionnaire as well as the self-made questionnaire for their commitment to health behavior were completed. Data were analyzed using multiple linear regression and Pearson correlation coefficient by SPSS software version 22 and STATA version 13. Results: Multiple linear regression analysis showed that crude and adjusted odds ratio of religious commitment in a prediction of commitment to health were 1.53 and 1.68 respectively. Among four independent variables, education, gender, and occupation were not good predictors for health commitments (P> 0.05) and only age was significant (p<0.05). Conclusion: It seems that in the current situation, the commitment to health behaviors is a consequence of the commitment to religious behavior and other factors. Therefore, the combined role of religious commitment and other factors should not be overlooked in the pathology of health behaviors.